Design and Analysis of a New Deployer for the in Orbit Release of Multiple Stacked CubeSats - Yong Zhao; Honghao Yue; Xingke Mu; Xiaoze Yang; Fei Yang (Remote Sensing, 2022)
More and more CubeSats cooperate to implement complex space exploration missions. In order to store and deploy more CubeSats in a rocket-launch mission, this paper presents a new CubeSat deployer with large-capacity storage. Different from the traditional one with the compression springs, the deployer with electromagnetic actuators is proposed to achieve the transportation and release. A new electromagnetic actuator with high thrust density was applied to adjust the release speeds of the CubeSats with different masses, and a new electromagnetic convey platform with attractive force was designed to transfer the stacked CubeSats to the release window. The equivalent magnetic circuit method was used to the establish electromagnetic force models. The simplified dynamic models of the transportation and release were built. The magnetic field, electromagnetic force, and motion characteristics were analyzed. The prototype was developed to verify the performance of the proposed configuration of the deployer with electromagnetic actuators. The experimental results show that stacked CubeSats can be transported smoothly even under constant external interference. The launcher achieved high thrust density and effectively adjusted the separation speed of the CubeSats.